Circulating MicroRNAs in Plasma Decrease in Response to Sarcopenia in the Elderly - He, Nana; Zhang, Yue Lin; Zhang, Yue; Feng, Beili; Zheng, Zaixing; Wang, Dongjuan; Zhang, Shun; Guo, Qi; Ye, Honghua (Frontiers in Genetics, 2020)
sarcopenia has been defined as the aging-related disease with the declined mass, strength, and function of skeletal muscle, which is a major cause of morbidity and mortality in elders. Current diagnostic criteria of sarcopenia have not been agreed internationally, and the clinical diagnostic biomarkers for sarcopenia have not been identified. Circulating miRNAs (miRNAs, miRs) have recently been characterized as novel biomarkers for sarcopenia. However, the change of circulating miRNAs in response to sarcopenia are still not fully understood. Here, we enrolled a total of 93 elderly patients clinically diagnosed with sarcopenia and matching 93 non-sarcopenia elderly in this study. Specifically, levels of candidate circulating miRNAs which were involved in angiogenesis, inflammation and enriched in muscle and/or cardiac tissues were detected in these two groups. In small-sample screening experiments, plasma miR-155, miR-208b, miR-222, miR-210, miR-328 and miR-499 levels were significantly down-regulated in sarcopenia compared to those who non-sarcopenia. In contrast, miR-1, mir-133a, miR-133b, miR-21, miR-146a, miR-126, miR-221 and miR-20a were not changed significantly. Subsequently, we expanded the sample size to further detection and verification, and found that plasma miR-155, miR-208b, miR-222, miR-210, miR-328, and miR-499 levels in the sarcopenia group were significantly reduced compared to the non-sarcoma group, which is consistent with the results of the small-sample screening experiment. In addition, we showed that ASM/Height2, handgrip strength, knee extension and 4-meter velocity in sarcopenia group were significantly lower than those in non-sarcopenia group. Here we correlated the decrease of miR-208b, miR-499, miR-155, miR-222, miR-328 and miR-210 in sarcopenia group and non-sarcopenia group with diagnostic indexes of sarcopenia (ASM/Height2, Handgrip strength and 4-meter velocity) after adjusting sex. The results showed that miR-208b and miR-155 changes were significantly correlated with handgrip strength in woman, miR-208b, miR-499 and miR-222 changes were significantly correlated with ASM/Height2 in man. In conclusion, plasma miR-208b, miR-499, miR-155, miR-222, miR-328 and miR-210 decrease in response to sarcopenia in the elderly. Although further studies are needed to clarify the potential use of circulating miRNAs as biomarkers of sarcopenia, present findings set the stage for defining circulating miRNAs as biomarkers and suggesting their physiological roles in elderly with sarcopenia.